Preparation method of high-temperature-resistant bio-based nylon with controllable molecular weight

Through the steps of prepolymerization and polycondensation reaction, high-temperature resistant biomass nylon with controllable molecular weight is prepared, which solves the problem of uncontrollable molecular weight in the prior art and improves the stability and performance of the product.

CN119463160APending Publication Date: 2025-02-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411721216.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The molecular weight of existing high-temperature resistant biomass nylon is uncontrollable, affecting its wide application in various fields.

Method used

By mixing bio-based nylon salt with water and performing prepolymerization, a prepolymer is obtained, and then pulverizing and sieving under a protective atmosphere to obtain a prepolymer powder, and then undergoing polycondensation reaction to prepare a controllable molecular weight resistance High temperature biomass nylon polymer.

Benefits of technology

The molecular weight of high-temperature resistant biomass nylon is achieved, the stability of the preparation process is improved, and a nylon polymer with specific molecular weight and properties is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463160A_ABST
    Figure CN119463160A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-temperature-resistant bio-based nylon with controllable molecular weight, and belongs to the technical field of bio-based high polymer materials. The bio-based nylon is prepared through prepolymerization and polycondensation, the prepolymer is crushed into powder with different mesh numbers and sizes to obtain the prepolymer powder with large specific surface area, small particle size and uniform distribution, and the prepolymer with excellent stability is obtained by controlling the mesh number and the uniformity degree of the prepolymer, so that the stability of the preparation process of the high-temperature-resistant nylon is improved; and then through pre-polymerization and polycondensation solid phase tackifying, the high-temperature-resistant bio-based nylon with controllable molecular weight and narrow distribution is obtained, and the problem that the molecular weight of the high-temperature-resistant nylon is uncontrollable is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bio-based polymer materials, and in particular to a method for preparing high-temperature-resistant bio-based nylon with controllable molecular weight. Background Art

[0002] Polyamide, commonly known as nylon, has good heat resistance of fully aromatic nylon, but its melting temperature is much higher than its initial thermal decomposition temperature, and it cannot be melted and injection molded. Semi-aromatic nylon is made by the condensation reaction of aliphatic diamine and aromatic diacid or aliphatic diacid and aromatic diamine. Compared with aliphatic nylon or fully aromatic nylon, it has excellent heat resistance and melt processing characteristics, which has attracted the attention of researchers.

[0003] Nylon 6T is the most widely used semi-aromatic heat-resistant nylon, but its main raw material hexamethylenediamine is a petroleum-based product. The rapid consumption of fossil resources and its adverse impact on the environment require the use of bio-based materials to replace petrochemical products. Pentamethylenediamine is similar to hexamethylenediamine in structure and can be enzymatically synthesized from lysine through cell biotransformation, or directly prepared by biological fermentation. The development of a new bio-based heat-resistant nylon 5T using pentamethylenediamine as a raw material has significant social and economic benefits and can reduce carbon emissions. However, the melting temperature of nylon 5T is close to its initial decomposition temperature, indicating that the processing window of nylon 5T (the temperature gap between the melting point and the starting point of degradation) is very narrow, so decomposition occurs during melt processing, which is unfavorable to product performance. Generally, the properties of polymers can be improved by molecular design through copolymerization modification to facilitate molding and processing. For example, a flexible nylon 10T unit is introduced into the nylon 5T molecular chain to obtain a nylon 5T / 10T copolymer with a wider processing window. However, since the polymerization steps of high-temperature resistant nylon are relatively large, the polymerization temperature and polymerization pressure are relatively high, the polymerization process is difficult to control, and the molecular weight of the prepared high-temperature resistant nylon is uncontrollable, which affects its wide application in various fields. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing high-temperature resistant bio-based nylon with controllable molecular weight, so as to achieve stable and controllable molecular weight of high-temperature resistant bio-based nylon.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing high temperature resistant bio-based nylon with controllable molecular weight, comprising the following steps:

[0007] mixing a bio-based nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer;

[0008] The prepolymer is crushed and sieved in sequence to obtain a prepolymer powder;

[0009] Under a protective atmosphere, the prepolymer powder is subjected to a polycondensation reaction to obtain a high temperature resistant bio-based nylon polymer;

[0010] The bio-based nylon salt includes a semi-aromatic bio-based nylon salt;

[0011] The mesh number of the prepolymer powder is 5 to 325 meshes.

[0012] Preferably, the bio-based nylon salt also includes aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt.

[0013] Preferably, the molar ratio of the semi-aromatic bio-based nylon salt to the aliphatic bio-based nylon salt is 1:9 to 9:1.

[0014] Preferably, the mass fraction of the nylon salt solution is 30-90%.

[0015] Preferably, the additives include at least one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent.

[0016] Preferably, the mass of the additive is 0.01 to 1.5 wt.% of the mass of the nylon salt solution.

[0017] Preferably, the prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 h.

[0018] Preferably, the mesh size of the prepolymer powder is 5-100 mesh, 100-150 mesh, 150-200 mesh, 200-300 mesh or 300-325 mesh.

[0019] Preferably, the polycondensation reaction is carried out at a temperature of 220 to 300° C., for a time of 4 to 20 hours, at a vacuum degree of 100 to 1,000,000 Pa, and at a stirring speed of 20 to 120 r / min.

[0020] Preferably, the molecular weight of the high temperature resistant bio-based nylon is 20,000 to 40,000 g / mol.

[0021] The invention provides a method for preparing a high-temperature resistant bio-based nylon with controllable molecular weight. The invention prepares the bio-based nylon by prepolymerization and polycondensation, crushes the prepolymer into powders with different mesh sizes, obtains a prepolymer powder with large specific surface area, small particle size and uniform distribution, controls the mesh size and uniformity of the prepolymer, realizes good controllability and repeatability of the molecular weight distribution of the prepolymer, controls the reaction conditions of the polycondensation process to remain unchanged, controls the mesh size and uniformity of the prepolymer, realizes controllable molecular weight of the nylon polymer, thereby obtains a nylon polymer with specific molecular weight and performance, and solves the problem of uncontrollable molecular weight of high-temperature resistant nylon.

[0022] In addition, the present invention can obtain a prepolymer with excellent stability by controlling the mesh size of the prepolymer, thereby improving the stability of the process of preparing high-temperature resistant nylon, and then obtain high-temperature resistant bio-based nylon with controllable molecular weight and narrow distribution through polycondensation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The nylon 5T / 56 copolymer prepared in Example 3 1 H NMR spectrum;

[0024] Figure 2 The nylon 5T / 56 copolymer prepared in Example 3 13 C NMR spectrum;

[0025] Figure 3 FTIR spectra of nylon 5T / 54, nylon PA5T / 56 and nylon PA5T / 510 copolymers prepared in the examples;

[0026] Figure 4 XRD spectra of nylon 5T / 54, nylon PA5T / 56 and nylon PA5T / 510 copolymers prepared in the examples. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing high temperature resistant bio-based nylon with controllable molecular weight, comprising the following steps:

[0028] mixing a bio-based nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer;

[0029] The prepolymer is crushed and sieved in sequence to obtain a prepolymer powder;

[0030] Under a protective atmosphere, the prepolymer powder is subjected to a polycondensation reaction to obtain a high temperature resistant bio-based nylon polymer;

[0031] The bio-based nylon salt includes a semi-aromatic bio-based nylon salt;

[0032] The mesh number of the prepolymer powder is 5 to 325 meshes.

[0033] The invention mixes bio-based nylon salt and water, mixes the obtained nylon salt solution with additives, performs prepolymerization reaction, and obtains a prepolymer.

[0034] In the present invention, the bio-based nylon salt preferably also includes aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt preferably includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt preferably includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt. When the above-mentioned nylon salt is two or more of the above-mentioned, the present invention has no special limitation on the ratio of different types of nylon salts, which can be adjusted according to actual needs. The benzene ring unit structure contained in the main chain of the semi-aromatic copolymer nylon macromolecule in the present invention gives it high temperature resistance.

[0035] In the present invention, when the bio-based nylon salt is a semi-aromatic bio-based nylon salt and an aliphatic bio-based nylon salt, the molar ratio of the semi-aromatic bio-based nylon salt to the aliphatic bio-based nylon salt is preferably 1:9 to 9:1, more preferably 1:1, 3:7, 2:8, 4:6, 7:3 or 9:1.

[0036] The present invention has no particular limitation on the preparation method of the bio-based nylon salt, and the bio-based nylon salt can be prepared by using corresponding bio-based diamine and bio-based diacid according to methods well known in the art.

[0037] In the present invention, the preparation method of the bio-based nylon salt is preferably: under normal pressure and protective atmosphere, dissolving the diacid in water at 50-100° C. (more preferably 70-80° C.) to obtain an acid solution with a mass concentration of 30-80% (more preferably 50-60%); dissolving the bio-based diamine in water at room temperature to obtain an amine solution with a mass concentration of 30-80% (more preferably 40-50%); adding the amine solution to the acid solution under stirring (the molar ratio of the amine group in the amine solution to the carboxyl group in the acid solution is preferably 1-1.1:1, more preferably 1.02-1.04:1), maintaining the temperature at 40-90° C. (more preferably 70-80° C.), continuously stirring for 0.5-2h, cooling the obtained mixed solution to 0-20° C. (more preferably 5-10° C.), standing for 1-4h (more preferably 2-3h), filtering, washing and drying the precipitated crystals to obtain nylon 5T salt. The gas used for the protective atmosphere is preferably at least one of nitrogen, argon, helium and carbon dioxide, more preferably at least one of nitrogen, argon and helium, more preferably nitrogen and argon; the present invention has no special limitation on the ratio of different gases, which can be adjusted according to needs.

[0038] In the present invention, the mass fraction of the nylon salt solution is preferably 30-90%, more preferably 40-80%, and further preferably 60-70%. The present invention uses water as a solvent, which is convenient for adding materials in the prepolymerization step, plays a role of a dispersion medium, and promotes mass transfer and heat transfer, making the prepolymerization process more stable, and then after the prepolymerization is completed, the excess water is removed by reducing the pressure to further increase the polymer molecular weight.

[0039] In the present invention, the additives preferably include at least one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent; when the additives are two or more of the above, the present invention has no special limitation on the ratio of different types of additives, which can be adjusted according to actual needs.

[0040] In the present invention, the mass of the additive is preferably 0.01 to 1.5 wt.% of the mass of the nylon salt solution, more preferably 0.2 to 0.6 wt.%, and further preferably 0.3 to 0.4 wt.%.

[0041] In the present invention, the catalyst preferably includes one or more of anhydrous sodium hypophosphite, anhydrous potassium hypophosphite, anhydrous sodium phosphite and anhydrous potassium phosphite, and the addition amount thereof (relative to the nylon salt solution) is preferably 0.01-0.8wt.%, more preferably 0.1-0.7wt.%, and further preferably 0.2-0.3wt.%; the antioxidant preferably includes hindered phenol antioxidants and / or amine antioxidants, and the addition amount thereof (relative to the nylon salt solution) is preferably 0.01-0.1wt.%, more preferably 0.03-0.05wt.%; the hindered phenol antioxidants are preferably 1010 and / or 1076; the amine antioxidants are preferably naphthylamine and / or diphenylamine; the end-capping agent preferably includes one or more of acetic acid, hexanoic acid, benzoic acid and hexylamine, and the addition amount thereof (relative to the nylon salt solution) is preferably 0.1%-1wt.%, more preferably 0.3-0.6wt.%, and further preferably 0.5wt.%.

[0042] In the present invention, the antistatic agent preferably includes one or more of quaternary phosphonium salt type cationic antistatic agent, quaternary ammonium salt type cationic antistatic agent and alkyl sulfate type anionic antistatic agent; the weathering agent preferably includes one or more of hydroquinone compounds, benzotriazole compounds and benzophenone compounds; the nucleating agent preferably includes one or more of silicon dioxide, clay, boron nitride, high melting point nylon and metal oxides; the flame retardant preferably includes one or more of magnesium hydroxide, brominated polystyrene, brominated polycarbonate and ammonium polyphosphate; the matting agent preferably includes titanium dioxide. The present invention has no special restrictions on the specific model of each additive, and the corresponding additives well known in the art can be used.

[0043] The present invention preferably adds water to the bio-based nylon salt, adds additives to the obtained nylon salt solution, replaces the air in the stainless steel high-pressure reactor with a protective gas 5 times, and stirs for 1.5 to 3 hours at 70 to 80° C. and 0.5 MPa in a protective atmosphere to completely dissolve the nylon salt, thereby performing a prepolymerization reaction; the protective atmosphere is the same as above.

[0044] In the present invention, the temperature of the prepolymerization reaction is preferably 200-240°C, more preferably 220-235°C, and further preferably 225-230°C; the pressure is preferably 1.5-2.3 MPa, more preferably 1.8-2.4 MPa, and further preferably 2.0-2.1 MPa; the time is preferably 0.5-5 h, more preferably 2-4 h, and further preferably 3-3.5 h.

[0045] After the prepolymerization reaction is completed, the present invention preferably reduces the pressure to 0.001 MPa so that more than 98% of the water in the system is discharged; after cooling, a prepolymer is obtained.

[0046] After obtaining the prepolymer, the present invention sequentially pulverizes and sieves the prepolymer to obtain prepolymer powder.

[0047] In the present invention, the mesh size of the prepolymer powder is 5 to 325 meshes, more preferably 5 to 100 meshes, 100 to 150 meshes, 150 to 200 meshes, 200 to 300 meshes or 300 to 325 meshes.

[0048] The present invention preferably performs pulverization in a FW-200 high-speed universal pulverizer, and uses sample sieves of different specifications (corresponding to mesh numbers) for sieving to obtain prepolymer powder.

[0049] After obtaining the prepolymer powder, the present invention performs a polycondensation reaction on the prepolymer powder under a protective atmosphere to obtain a high temperature resistant bio-based nylon polymer.

[0050] The present invention preferably washes the prepolymer powder with anhydrous ethanol and then dries it, and then heats it to the temperature of the polycondensation reaction while stirring it to carry out the polycondensation reaction; the drying method is preferably one or more of vacuum drying, freeze drying, airflow drying, microwave drying, infrared drying and high-frequency drying; the present invention has no special limitation on different drying methods, and can be adjusted according to demand. The present invention washes and dries the prepolymer powder with anhydrous ethanol to remove impurities such as residual nylon salt, monomer, small molecule oligomer and detergent, which is conducive to the stability of the quality of the polymer product.

[0051] In the present invention, the gas used for the protective atmosphere is preferably at least one of nitrogen, argon, helium and carbon dioxide, and more preferably at least one of nitrogen, argon and helium. The present invention has no special limitation on the ratio of different gases, which can be adjusted according to demand.

[0052] In the present invention, the temperature of the polycondensation reaction is preferably 220-300°C, more preferably 240-280°C, and further preferably 250-260°C; the time is preferably 4-20h, more preferably 6-16h, and further preferably 7-12h; the vacuum degree is preferably 100-1000000Pa, more preferably 500-10000Pa, and further preferably 800-1000Pa; the stirring speed is preferably 20-120r / min, more preferably 40-100r / min, and further preferably 50-80r / min.

[0053] After the polycondensation reaction is completed, the heating is stopped, the mixture is naturally cooled to room temperature, and the mixture is discharged to obtain a high temperature resistant bio-based nylon polymer.

[0054] In the present invention, the molecular weight of the high temperature resistant bio-based nylon is preferably 20000-40000 g / mol, more preferably 32599-37458 g / mol, and further preferably 35861-35183 g / mol.

[0055] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described below in conjunction with specific examples and comparative examples. All technical schemes and improvements thereof that do not depart from the present invention should be included in the scope of the claims of the present invention. It should be noted that, unless otherwise specified, the experimental reagents and equipment involved in the implementation of the present invention are all commonly used ordinary reagents and equipment, and the technical terms or scientific terms used in the present invention should be the usual meanings understood by technicians in the field to which the present invention belongs.

[0056] The present invention uses the following method to measure performance:

[0057] 1. Weight average molecular weight and polydispersity index

[0058] The molecular weight and distribution were determined by gel permeation chromatography (GPC) with hexafluoroisopropanol as the mobile phase and RI-UV as the detector.

[0059] 2. Relative viscosity

[0060] Weigh the dried high-temperature resistant bio-based polyamide and dissolve it in 96% concentrated sulfuric acid to make a solution with a mass concentration of 0.01g / mL. Test the time it takes for the liquid to flow through the two scale lines of the glass ball of the Ubbelohde viscometer in a constant temperature water bath at 25±0.02℃. Repeat the measurement three times. The difference between the three measured values ​​is no more than 0.1s, and the average value is taken. The ratio of the outflow time t2 of the polyamide solution to the outflow time t1 of the pure solvent is the relative viscosity, and the relative viscosity of the sample is calculated according to the formula η=t2 / t1.

[0061] 3. Melting point

[0062] Under a nitrogen flow rate of 50 mL / min, the temperature was raised from room temperature to 350°C at a heating and cooling rate of 10°C / min, kept constant for 3 min, then dropped to room temperature, and then raised to 350°C. The endothermic peak temperature of the secondary melting curve was set as the melting point.

[0063] 4. Decomposition temperature

[0064] Under nitrogen conditions, the heating rate was 10°C / min and the temperature was increased from 30°C to 800°C.

[0065] 5. Yellow index

[0066] The yellowness index is determined according to HG / T 3862-2006 method.

[0067] 6. Tensile properties

[0068] Under the conditions of temperature 25°C and relative humidity 75%, the tensile property test method is carried out according to the national standard GB / T 1040-2008, and the test speed is 50mm / min.

[0069] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] Under normal pressure and nitrogen purge conditions, 352.48 g of terephthalic acid was weighed and dissolved in pure water at 80° C. to prepare a terephthalic acid suspension with a mass fraction of 60%; at the same time, 221.89 g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 40%; then, the pentamethylenediamine solution was added to the phthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.02) under stirring conditions of 300 r / min, the temperature was maintained at 80° C., and after continuous stirring for 2 hours, the obtained mixed solution was cooled to 10° C. and allowed to stand for 3 hours, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt;

[0072] According to the above reaction steps, succinic acid and pentamethylenediamine are used as reaction monomers (the molar ratio of carboxyl group to amine group is 1:1.02) to obtain nylon 54 salt;

[0073] Weigh a total of 931.60 g of dried nylon 5T salt and nylon 54 salt (molar ratio 1:1) and put them into a 20L stainless steel autoclave, add 621.07 g of pure water to make the mass fraction of the nylon salt solution 60%, then add 2.3290 g of catalyst anhydrous sodium hypophosphite and 0.7763 g of antioxidant 1010, replace the air in the autoclave with nitrogen for 5 times, and stir for 1.5 h at 80° C. and 0.5 MPa nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 220° C. and the pressure to 2.1 MPa to carry out prepolymerization for 3.5 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain a nylon 5T / 54 prepolymer, put it into a FW-200 high-speed universal crusher for crushing, and pass through a 5-mesh and 100-mesh sample sieve to obtain a prepolymer powder with a particle size of 5 to 100 mesh;

[0074] The prepolymer powder was washed with anhydrous ethanol and dried in vacuum, and then added into a polymerization kettle. The mixture was heated to 260°C at 80 r / min under nitrogen purge, and then evacuated to a vacuum degree of 1000 Pa. The mixture was kept warm for 4 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5T / 54 polymer was obtained after discharge.

[0075] The relative molecular weight (Mw) of the nylon polymer prepared in Example 1 is 32599 g / mol, the polydispersity index is 1.23, the relative viscosity is 2.08, the melting point is 303° C., the initial decomposition temperature is 394° C., the tensile strength is 56.5 MPa, and the color is slightly white and transparent.

[0076] Example 2

[0077] Under normal pressure and nitrogen purging conditions, 345.68g of isophthalic acid was weighed and dissolved in pure water at 80°C to prepare an isophthalic acid suspension with a mass fraction of 60%; at the same time, 216.24g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 40%; then, the pentamethylenediamine solution was added to the isophthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.02) under stirring at 300r / min, the temperature was maintained at 80°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 10°C and allowed to stand for 3h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, succinic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.02) to obtain nylon 54 salt;

[0078] Weigh a total of 950.15 g of dried nylon 5I salt and nylon 54 salt (molar ratio 3:7) and put them into a 20L stainless steel autoclave, add 407.21 g of pure water to make the mass fraction of nylon salt 70%, then add 6.7869 g of catalyst anhydrous sodium hypophosphite and 6.7868 g of end-capping agent benzoic acid, replace the air in the autoclave with nitrogen for 5 times, stir for 1.5 h at 80 ° C and 0.5 MPa nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 220 ° C and the pressure to 2.0 MPa to carry out prepolymerization for 4 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain nylon 5I / 54 prepolymer, put it into FW-200 high-speed universal crusher for crushing, pass through 100 mesh and 150 mesh sample sieves, and obtain prepolymer powder with a particle size of 100-150 mesh;

[0079] The prepolymer powder was washed with anhydrous ethanol and freeze-dried, and then added to a polymerization kettle. Under nitrogen purge, the mixture was heated to 260°C at 100 r / min with stirring, and then evacuated to 800 Pa. The mixture was kept warm for 4 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5I / 54 polymer was obtained after discharge.

[0080] The relative molecular weight (Mw) of the nylon polymer prepared in Example 2 is 35861 g / mol, the polydispersity index is 1.16, the relative viscosity is 2.15, the melting point is 304° C., the initial decomposition temperature is 394° C., the tensile strength is 56.7 MPa, and the color is slightly white and transparent.

[0081] Example 3

[0082] Under normal pressure and argon purging conditions, 355.63g of terephthalic acid was weighed and dissolved in pure water at 80°C to prepare a terephthalic acid suspension with a mass fraction of 60%; at the same time, 227.08g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 40%; then the pentamethylenediamine solution was added to the terephthalic acid solution under stirring at 300r / min (the molar ratio of carboxyl group to amine group was 1:1.04), the temperature was maintained at 80°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 10°C and allowed to stand for 3h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, adipic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.04) to obtain nylon 56 salt;

[0083] Weigh a total of 952.30 g of dried nylon 5T salt and nylon 56 salt (molar ratio 2:8) and put them into a 20L stainless steel autoclave, add 1429.08 g of pure water to make the mass fraction of nylon salt 40%, then add 6.3487 g of catalyst anhydrous potassium hypophosphite and 0.9523 g of antioxidant 1076, replace the air in the autoclave with argon gas 5 times, stir for 2 hours at 80°C and 0.5 MPa argon atmosphere to completely dissolve the nylon salt; raise the temperature to 230°C and the pressure to 2.3 MPa to carry out prepolymerization for 3 hours; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain nylon 5T / 56 prepolymer, put it into FW-200 high-speed universal crusher for crushing, pass through 150 mesh and 200 mesh sample sieves, and obtain prepolymer powder with a particle size of 150-200 mesh;

[0084] The prepolymer powder was washed with anhydrous ethanol and dried by microwave, and then added into a polymerization kettle. The temperature was raised to 250°C at 120 r / min with stirring under argon purge, and then evacuated to a vacuum degree of 1200 MPa. The mixture was kept warm for 6 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5T / 56 polymer was obtained after discharging.

[0085] The relative molecular weight (Mw) of the nylon polymer prepared in Example 3 is 35183 g / mol, the polydispersity index is 1.19, the relative viscosity is 2.14, the melting point is 303° C., the initial decomposition temperature is 401° C., the tensile strength is 57.9 MPa, and the color is slightly white and transparent.

[0086] Example 4

[0087] Under normal pressure and nitrogen purging conditions, 335.18 g of isophthalic acid was weighed and dissolved in pure water at 70° C. to prepare an isophthalic acid suspension with a mass fraction of 50%; at the same time, 215.18 g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 50%; then, the pentamethylenediamine solution was added to the isophthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.04) under stirring at 350 r / min, the temperature was maintained at 70° C., and after continuous stirring for 2 hours, the obtained mixed solution was cooled to 5° C. and allowed to stand for 1 hour. The precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, adipic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.04) to obtain nylon 56 salt;

[0088] Weigh a total of 966.07 g of dried nylon 5I salt and nylon 56 salt (molar ratio 4:6) and put them into a 20L stainless steel autoclave, add 965.97 g of pure water to make the mass fraction of nylon salt 50%, then add 6.0519 g of catalyst anhydrous sodium hypophosphite and 5.8051 g of end-capping agent caproic acid, replace the air in the autoclave with nitrogen for 5 times, stir for 3 hours at 70°C and 0.5 MPa nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 225°C and the pressure to 1.8 MPa to carry out prepolymerization for 5 hours; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain nylon 5I / 56 prepolymer, put it into FW-200 high-speed universal crusher for crushing, pass through 200 mesh and 300 mesh sample sieves, and obtain prepolymer powder with a particle size of 200-300 mesh;

[0089] The prepolymer powder was washed with anhydrous ethanol and dried in vacuum, and then added into a polymerization kettle. The mixture was heated to 260°C at 120 r / min under nitrogen purge, and then evacuated to a vacuum degree of 100 Pa. The mixture was kept warm for 7 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5I / 56 polymer was obtained after discharging.

[0090] The relative molecular weight (Mw) of the nylon polymer prepared in Example 4 is 37458 g / mol, the polydispersity index is 1.37, the relative viscosity is 2.25, the melting point is 304° C., the initial decomposition temperature is 400° C., the tensile strength is 57.3 MPa, and the color is slightly white and transparent.

[0091] Example 5

[0092] Under normal pressure and nitrogen purge conditions, 318.34 g of terephthalic acid was weighed and dissolved in pure water at 80° C. to prepare a terephthalic acid suspension with a mass fraction of 40%; at the same time, 199.48 g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 60%; then, the pentamethylenediamine solution was added to the terephthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.02) under stirring at 300 r / min, the temperature was maintained at 80° C., and after continuous stirring for 1.5 hours, the obtained mixed solution was cooled to 8° C. and allowed to stand for 3 hours. The precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.02) to obtain nylon 510 salt;

[0093] Weigh a total of 959.08 g of dried nylon 5T salt and nylon 510 salt (molar ratio 7:3) and put them into a 20L stainless steel autoclave, add 516.43 g of pure water to make the mass fraction of nylon salt 65%, then add 5.5075 g of catalyst anhydrous sodium phosphite and 0.8007 g of antioxidant naphthylamine, replace the air in the autoclave with nitrogen for 5 times, stir for 1.5 h at 80 ° C and 0.5 MPa nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 200 ° C and the pressure to 1.9 MPa to carry out prepolymerization for 2 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain nylon 5T / 510 prepolymer, put it into FW-200 high-speed universal crusher for crushing, pass through 300 mesh and 325 mesh sample sieves, and obtain prepolymer powder with a particle size of 300-325 mesh;

[0094] The prepolymer powder was washed with anhydrous ethanol and freeze-dried, and then added to a polymerization kettle. The mixture was heated to 280°C at 60 r / min while being stirred under nitrogen purge, and then evacuated to a vacuum degree of 1300 Pa. The mixture was kept warm for 16 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5T / 510 polymer was obtained after discharging.

[0095] The relative molecular weight (Mw) of the nylon polymer prepared in Example 5 is 38441 g / mol, the polydispersity index is 1.07, the relative viscosity is 2.52, the melting point is 305° C., the initial decomposition temperature is 403° C., the tensile strength is 58.1 MPa, and the color is slightly white and transparent.

[0096] Example 6

[0097] Under normal pressure and argon purging conditions, 361.05g of isophthalic acid was weighed and dissolved in pure water at 80°C to prepare a terephthalic acid suspension with a mass fraction of 50%; at the same time, 244.27g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a pentamethylenediamine solution with a mass fraction of 50%; then, the pentamethylenediamine solution was added to the isophthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.1) under stirring at 300r / min, the temperature was maintained at 80°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 5°C and allowed to stand for 1h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.1) to obtain nylon 510 salt;

[0098] Weigh a total of 963.01 g of dried nylon 5I salt and nylon 510 salt (molar ratio 9:1) and put them into a 20L stainless steel autoclave, add 107.01 g of pure water to make the mass fraction of nylon salt 90%, then add 8.0705 g of catalyst anhydrous potassium phosphite and 6.5107 g of end-capping agent hexylamine, replace the air in the autoclave with argon for 5 times, stir for 1.5 h at 80° C. and 0.5 MPa argon atmosphere to completely dissolve the nylon salt; raise the temperature to 200° C. and the pressure to 1.5 MPa to carry out prepolymerization for 5 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system; after cooling, obtain nylon 5I / 510 prepolymer, put it into FW-200 high-speed universal crusher for crushing, pass through 300 mesh and 325 mesh sample sieves, and obtain prepolymer powder with a particle size of 300-325 mesh;

[0099] The prepolymer powder was washed with anhydrous ethanol and dried in vacuum, and then added into a polymerization kettle. The mixture was heated to 300°C at 70 r / min with stirring under argon purge, and then evacuated to a vacuum degree of 10000 Pa. The mixture was kept warm for 18 hours, and the heating was stopped. The mixture was naturally cooled to room temperature, and a high-temperature resistant bio-based nylon 5I / 510 polymer was obtained after discharging.

[0100] The relative molecular weight (Mw) of the nylon polymer prepared in Example 6 is 39015 g / mol, the polydispersity index is 1.09, the relative viscosity is 2.43, the melting point is 306° C., the initial decomposition temperature is 401° C., the tensile strength is 57.8 MPa, and the color is slightly white and transparent.

[0101] Structural characterization

[0102] Figure 1 The nylon 5T / 56 copolymer prepared in Example 3 1 HNMR spectrum; Figure 2 The nylon 5T / 56 copolymer prepared in Example 3 13 C NMR spectrum; Figures 1-2 The successful synthesis of the copolymer can be demonstrated.

[0103] Figure 3 FTIR spectra of nylon 5T / 54, nylon PA5T / 56 and nylon PA5T / 510 copolymers prepared in the examples; Figure 4 XRD spectra of nylon 5T / 54, nylon PA5T / 56 and nylon PA5T / 510 copolymers prepared in the examples. Figures 3-4 The successful synthesis of the corresponding copolymers can be demonstrated.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high temperature resistant bio-based nylon with controllable molecular weight, comprising the following steps: mixing a bio-based nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer; The prepolymer is crushed and sieved in sequence to obtain a prepolymer powder; Under a protective atmosphere, the prepolymer powder is subjected to a polycondensation reaction to obtain a high temperature resistant bio-based nylon polymer; The bio-based nylon salt includes a semi-aromatic bio-based nylon salt; The mesh number of the prepolymer powder is 5 to 325 meshes.

2. The preparation method according to claim 1, characterized in that: The bio-based nylon salt also includes aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the semi-aromatic bio-based nylon salt to the aliphatic bio-based nylon salt is 1:9 to 9:

1.

4. The preparation method according to claim 1, characterized in that: The mass fraction of the nylon salt solution is 30-90%.

5. The preparation method according to claim 1, characterized in that: The additives include at least one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent.

6. The preparation method according to claim 1, characterized in that: The mass of the additive is 0.01-1.5 wt.% of the mass of the nylon salt solution.

7. The preparation method according to claim 1, characterized in that: The prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 hours.

8. The preparation method according to claim 1, characterized in that: The mesh numbers of the prepolymer powder are 5-100 meshes, 100-150 meshes, 150-200 meshes, 200-300 meshes or 300-325 meshes.

9. The preparation method according to claim 1, characterized in that: The temperature of the polycondensation reaction is 220-300° C., the time is 4-20 hours, the vacuum degree is 100-1000000 Pa, and the stirring speed is 20-120 r / min.

10. The preparation method according to claim 1, characterized in that: The molecular weight of the high temperature resistant bio-based nylon is 20000-40000 g / mol.

Citation Information

Patent Citations

  • Copolymerized aromatic-aliphatic semi-aromatic nylon and preparation method thereof

    CN112646174A

  • Continuous production method of high-temperature nylon powder with narrow molecular weight distribution

    CN116874771A

  • Method for preparing high-molecular-weight bio-based high-temperature-resistant nylon 5T by coupling salt solution polycondensation with solid phase polycondensation

    CN117986569A

  • Process for the preparation of polyamide prepolymers

    EP0410650A1